(untitled) (Research, Society and Development, 2022)
Introduction: Childhood obesity, according to the World Health Organization (WHO), has become a worldwide problem. The nutritional transition of the population began to interfere with weight, especially in women of childbearing age, increasing the chances of the emergence of gestational diabetes mellitus and, consequently, fetal macrosomia. Objective: to investigate macrosomic or large-for-gestational-age newborns and childhood obesity susceptibility. Methodology: This is a literature review with a descriptive objective and a qualitative approach, using the SciELO, LILACS and PubMed platforms, using the terms Macrosomia and “Child obesity”, published between the years 2006-2021, in Portuguese and English. corresponding to the objectives of the study. Among the 53 articles selected, only 25 were chosen after reading the abstracts for inclusion. Results and discussion: The assessment of pre-pregnancy BMI contributes to the diagnosis of the nutritional status of women to avoid the risks of morbidities for the mother-child binomial due to overweight and obesity. Gestational diabetes mellitus generates an increase in blood glucose by crossing the placental barrier to provide substrate for the baby, leading to a consequent increase in weight for gestational age. The association of maternal risk factors for fetal birth with macrosomia has the ability to generate long-term effects on childhood obesity, extending into adulthood. Conclusion: It was possible to evaluate that the birth of macrosomic babies has a higher percentage in relation to childhood obesity compared to newborns with adequate weight, corroborating through studies with pregnant women and neonates.